Copepod secondary production in the sea: Errors due to uneven molting and growth patterns and incidence of carcasses - Kam Tang (Progress in Oceanography, 2018)
Copepod secondary production is one of the most fundamental parameters in biological oceanography, but the common approach to estimate this parameter relies on two important, but rarely verified, assumptions: (1) even developmental stage duration and inter-molt growth; (2) all copepods are alive in situ. We conducted a year-long study within the Humboldt Current system to assess the errors in the secondary production estimation of three dominant copepod species when these assumptions are violated. The error varied in magnitude between months and even switched sign (over- vs. under-estimation) in some cases. The errors also varied in magnitude and in sign among developmental stages, reaching nearly 70% over-estimation in some cases. The annual average error was ca. -39% for Paracalanus cf. indicus, 3% for Acartia tonsa, and 5% for Calanus chilensis. Our study showed that careful assessment of species-specific stage duration, inter-stage growth and in situ live/dead abundances is required for more reliable secondary production estimation.